Increased Open‐Circuit Voltage of Organic Solar Cells by Reduced Donor‐Acceptor Interface Area. (24th March 2014) - Vandewal, Koen; Widmer, Johannes; Heumueller, Thomas; Brabec, Christoph J.; McGehee, Michael D.; Leo, Karl; Riede, Moritz; Salleo, Alberto
<x xml:space="preserve">Abstract</x> The charge carrier lifetime in small molecule: C60 photovoltaic devices is increased by reducing the physical interface area availabe for recombination. For donor contents below 10%, the gain in open‐circuit voltage (Voc) depends logarithmically on the interface area while the energy of the interfacial charge‐transfer state ECT remains invariant. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>